GREEDY SINGLE USER AND FAIR MULTIPLE USERS REPLICA SELECTION DECISION IN DATA GRID - JARADAT, AYMAN KAMEL SALIM (2013)
Replication in data grids increases data availability, accessibility and reliability. Replicas of datasets are usually distributed to different sites, and the choice of any replica locations has a significant impact. Replica selection algorithms decide the best replica places based on some criteria. To this end, a family of efficient replica selection systems has been proposed (RsDGrid). The problem presented in this thesis is how to select the best replica location that achieve less time, higher QoS, consistency with users' preferences and almost equal users' satisfactions. RsDGrid consists of three systems: A-system, D-system, and M-system. Each of them has its own scope and specifications. RsDGrid switches among these systems according to the decision maker.